Experimental investigation on using Al2O3/ethylene glycol-water nano-fluid in different types of horizontal ground heat exchangers - Kapicioglu, Abdullah; Esen, Hikmet (Pergamon-Elsevier Science Ltd, 2020)
This study presents the experimental results for the first time use of Al2O3/ethylene glycol-water (EG-water) nano-fluid (NF) in ground heat exchangers (GHE) within the ground source heat pump (GSHP) system which is prepared with 8 nm gamma-Al2O3 nanoparticles. A test room with an area of 21 m(2) was prepared in the cold climate region (39'42'24.8 '' N, 37'02'01.5 '' E) of Turkey, and GSHP system was installed into the room. Horizontal GHE designs are preferred as GHE design in order to maintain cost and efficiency balance. Although numerical studies on the use of NE-assisted fluids in GSHP systems are guiding in the literature, these studies have not been supported experimentally. In this study to see performance of NFs in real environment conditions Al2O3 nanoparticles were examined experimentally in horizontal U-type GHE and spiral GHE by adding different volume concentrations (0.1%, 0.2%) to EG-water (25-75%) base fluid. Our results showed that, with a volume concentration of 0.1%, NF provided a 19% and 22% increase compared to EG-water in U-type GHE and spiral GHE, respectively, concerning GHE output temperatures. In addition, the coefficient of performance (COP) of the system using NF with a volume concentration of 0.1% showed a higher performance of 2.5% in U-type GHE and 3% in spiral GHE compared to EG-water base fluid. On the other hand, in both GHE designs, the NF with a volume concentration of 0.2% did not achieve any performance increase. The NE with a volume concentration of 0.1%, which is the most successful variation of the U-type GHE and spiral GHE systems, showed a 2.7% higher COP value than the spiral GHE in U-type GHE. As a result, it has been determined that the use of low concentration of NF in GHEs for the GSHP system provides performance improvements independent of the GHE design.
Keywords: Nano-fluid; Aluminum oxide; Horizontal ground source heat pump; Heat exchange rate